Risk to residents, infrastructure, and water bodies from flash floods and sediment transport - Bauer, Miroslav; Dostal, Tomas; Krasa, Josef; Jachymova, Barbora; David, Vaclav; Devaty, Jan; Strouhal, Ludek; Rosendorf, Pavel (Environmental monitoring and assessment, 2019)
Intense rainfall-runoff events and subsequent soil erosion can cause serious damage to the infrastructure in residential areas in Europe countries and all over the world. In the Czech Republic, the Ministry of the Interior has supported an analysis dealing with the risks to residents, infrastructure, and water bodies from flash floods and sediment transport. A total of more than 150,000 risk points were identified by GIS morphology and land-use analysis. The threat, the vulnerability, and the resulting risk category were determined for each of these points. The WaTEM/SEDEM model was used to assess the threat with 10-m data resolution. The summarized vulnerability of real objects on individual runoff trajectories was combined with the threat of sediment transport, resulting in the overall risk represented by a 5-degree scale, from lowest (1) to highest (5). The output of the project lies stored in the WEB application. Nineteen percent of the sites in the Czech Republic, i.e., more than 23,000 sites, have been assigned to categories 4 and 5, with a high level of risk. Thirty-four percent of cadastral units are classified as the high risky (4416 cadasters, with a total area 24,707 km2). Approximately 30% of the population of the Czech Republic lives in high-risk cadastral areas. Four scenarios of protection were modeled. To reduce the high-risk and very high-risk sites (categories 4 and 5), the most effective solution is the implementation of technical measures or conversion to grassland within the contributing watersheds. This could reduce the number of high-risk sites from 23,400 to 3700.Methods of sediment transport modeling and risk evaluation, based on presented USLE input data and documented WaTEM/SEDEM model, can be used worldwide. Especially in post-soviet union countries with shared arable land development and erosion consequences.
Keywords: pohyb vody; geologické sedimenty; monitorování životního prostředí; Sediment transport; WaTEM/SEDEM; USLE; záplavy; Water Movements; Czech Republic; riziko; Environmental Monitoring; Disasters; Soil erosion; katastrofy; Česká republika; Geologic Sediments; Risk; Soil; půda; Pluvial flow; Floods